Spinal Reactive Oxygen Species and Oxidative Damage Mediate Chronic Pain in Lame Dairy Cows - Daniel Herzberg; Pablo Strobel; Ricardo Chihuailaf; Alfredo Ramirez-Reveco; Heine Müller; Marianne Werner; Hedie Bustamante (Animals, 2019)
Lameness in dairy cows is a worldwide prevalent disease with a negative impact on animal welfare and herd economy. Oxidative damage and antioxidant system dysfunction are common features of many CNS diseases, including chronic pain. The aim of this study was to evaluate the levels of reactive oxygen species (ROS) and oxidative damage markers in the spinal cord of dairy cows with chronic inflammatory lameness. Locomotion score was performed in order to select cows with chronic lameness. Dorsal horn spinal cord samples were obtained post mortem from lumbar segments (L2−L5), and ROS, malondialdehyde (MDA), and carbonyl groups were measured along with the activity of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and total antioxidant response (TAR). Lame cows had increased levels of ROS, MDA, and carbonyl groups, while no differences were observed between lame and non-lame cows in SOD, GPx, CAT, and TAR activity. We conclude that painful chronic inflammatory lameness in dairy cows is associated with an increase in ROS, MDA, and carbonyl groups. Nonetheless, an association between ROS generation and dysfunction of the antioxidant system, as previously proposed, could not be established.